Association of co-occurring psychosocial health conditions and HIV infection among MSM in Malaysia: Implication of a syndemic effect. (May 2020) - Ng, Rong Xiang; Guadamuz, Thomas E; Akbar, Mohd; Kamarulzaman, Adeeba; Lim, Sin How
In Malaysia, the HIV epidemic is concentrated in a highly stigmatized population, men who have sex with men (MSM). The relationship of multiple psychosocial health conditions and HIV risks have not been investigated. This study aims to assess the association of multiple psychosocial factors with risky sexual behaviour and HIV infection among MSM. Data on demographic characteristics, psychosocial health conditions, condomless anal intercourse (CAI), HIV testing and HIV status were collected via an anonymous online survey. Multivariable logistic regression model was used to determine whether psychosocial health conditions among MSM have a syndemic association with HIV status. Between July 2017 and February 2018, 622 MSM completed the online survey. Overall, 54.3% of participants reported engaging in CAI in the past three months and 46.0% were found to have two or more psychosocial health conditions. Increasing numbers of psychosocial health conditions (1, 2, 3, 4 or more) were significantly associated with HIV infection compared to those without psychosocial health condition (odds ratio [OR] 3.39, 95% confidence interval [CI]: 1.41–8.14; OR 3.51, 95% CI: 1.43–8.61; OR 4.22, 95% CI: 1.68–10.96, and OR 7.58, 95% CI: 2.44–23.55, respectively). Comprehensive HIV prevention programs addressing mental health and substance use are needed for MSM in Malaysia.